Effect of laser grooving on titanium dental implants surface composition: An in vitro study - Mohamed Ahmed Alkhodary (Wolters Kluwer Medknow Publications, 2024)
Introduction: The aluminum and vanadium contents of the titanium-aluminum-vanadium alloy (Ti-6Al-4V) surface are known to have cytotoxic effect, the use of laser grooving was thought to produce dental implants-controlled surface roughness and a better surface chemical composition. Aims: The aim of the current work was to test the titanium alloy machined and laser grooves surface content of the aluminum and vanadium, and their effect on cellular viability. Materials and Methods: Threaded titanium dental implants were designed, milled and micro-grooved using the Avia coherent pulsed ultraviolet laser and produced 10 µm grooves on their machined surface. The scanning electron microscope was used to evaluate the produced micro-grooves, and the X-ray diffraction to study the surface composition of the titanium alloy before and after laser grooving. And the MC3T3-E1 mouse osteoblasts were cultured on such surfaces to test their cytotoxic effect. Results and Discussion: The laser grooving significantly reduced the alloy surface content of the aluminum and vanadium as proved by the significantly better viability of the cells cultured on it as compared to the machined surface. Conclusion: The laser grooving reduced the Ti-6Al-4V alloy surface content of the cytotoxic elements.